Environmental factors regulating the population dynamics and reproductive strategy of freshwater mussel Parreysia corrugata in the Padma River, Bangladesh - Md Ayenuddin Haque; Rayhana Akhtar Raka; Md Raihan Ali; Md Jasim Uddin; Md Mostafizur Rahman Mondol (Heliyon)
Freshwater mussel Parreysia corrugata is an ecologically important species endemic to south-east Asia, which has been suffering from a dramatic decline in recent years. The present study investigated the population dynamics and reproductive strategy of P. corrugata in a changing climate of Bangladesh waters. Mussels were sampled monthly from January to December 2021 from the Padma River near the Rajshahi city of Bangladesh. A total of 809 specimens were collected with a sizes ranging from 36.07 to 101.41 mm shell length and 7.92–87.54 g weight, respectively. The mussels displayed a growth pattern characterized by negative allometry in body weight-shell length relationship. The asymptotic length (L∞) was 106.05 mm, the growth coefficient (K) was 0.370 per year, and the growth performance index (Φ′) was 3.58. The recruitment of P. corrugata was occurred throughout the year, with a peak during the month of February. The annual total mortality (Z) was 1.15, and natural mortality (M) and fishing mortality (F) were 0.61 and 0.54 per year, respectively. The exploitation level was E = 0.47 which indicates a state of under exploitation. Sex was identifiable throughout the study period and the sex ratio of the mussels did not differ significantly from the 1:1 (M: F) ratio ((χ2 = 15.80, P > 0.05). In terms of gonadal development, maturation, and spawning activity, both sexes had similar trends. Histology identified five gonad development stages for both male and female mussels: early developing, late developing, ripe, spawning, and spent. Monthly GSI data showed significant seasonal fluctuations with the highest GSI in April and it was sharply declined in May indicating the peak spawning of the mussels, which was in consistent with condition index and gonadal histology. All the physicochemical parameters showed significant variation except for pH. The most important factors explaining mussel body condition (b value) and reproductive strategies (GSI and CI) were water temperature, dissolved oxygen and water level. Although no known major threats of this species have been documented from Bangladesh, conservation measures could be adopted to protect the natural habitats of P. corrugata from adverse physicochemical and hydrological factors.